2012
DOI: 10.5539/ibr.v5n4p71
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Hofstede in Jordan: Ungeneralized, Reevaluating the Jordanian Culture

Abstract: Hofstede was credited with completing the largest cross-cultural study applicable to international management theory and a review of the literature indicates that the dimensions identified by Hofstede capture the essence of many dimensions and value orientations proposed by other researchers. The effect of culture on people's life is so great that it will even affects the motives and choices of people's behavior. The aim of the study is to update the Hofstede cultural value dimensions. We argue that scores (fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Due to the gap in the literature on cultural factors and management in Thai public sector, the researcher aims to identify the differences among the Thai public sector staff members, by adopting Hofstede's cultural dimensions to identify the pattern of culture in the Thai public sectors. Alkailani et al (2012) and Gong et al (2007) supported that Hofstede's model is still considered the most robust measure of national culture because of its substantial face validity. The researcher, thus, has adopted this model for the current study.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Due to the gap in the literature on cultural factors and management in Thai public sector, the researcher aims to identify the differences among the Thai public sector staff members, by adopting Hofstede's cultural dimensions to identify the pattern of culture in the Thai public sectors. Alkailani et al (2012) and Gong et al (2007) supported that Hofstede's model is still considered the most robust measure of national culture because of its substantial face validity. The researcher, thus, has adopted this model for the current study.…”
Section: Methodsmentioning
confidence: 71%
“…Fang (2010) proposed that Asians (including Thai) can be collectivistic thinking and actions may be prioritized and individual identities and initiatives may be dampened and invisible. Similarly, Alkailani et al (2012) also argued that assumption that people who grow up in the same place will share similar views about life does not apply to the contemporary organization.…”
Section: Discussionmentioning
confidence: 99%
“…For Jordan, the original numerical scores were inferred, since Hofstede only sampled five Arab countries and then generalised to include Jordan, but have not been radically challenged over the many subsequent studies by individual researchers, nor globally, for example, by the World Values Survey (http://www.worldvaluessurvey.org). A recent 'replication' of Hofstede's study (Alkailani et al, 2012) conducted in Jordan indicated that the dimensions of masculinity and individualism scores are indeed very similar to other Arab countries, though Jordan was relatively lower on the other two dimensions. The authors attributed this to a young and educated workforce, who is routinely consulted and unafraid to "disagree with their bosses".…”
Section: Hypothesis 5a: Low Lto Users Have Low Isf's Service Quality mentioning
confidence: 99%
“…The most recently developed theory, crossvergence advocates that the combination of socio-cultural influences and business ideology influences is the driving force that precipitates the development of new and unique value systems among individuals in a society owing to the dynamic interaction of these influences (Ralston et al 1993;Ralston, 2008). The reviews of cross-cultural studies suggest that Hofstede-inspired research is increasing exponentially (Taras et al 2010); not only a few researchers duplicated Hofstede"s study in order to approve his findings (e.g., Alkailani et al 2012;Bergiel et al 2012;Fischer and Al-Issa, 2012;Tantekin et al 2011;Baron, 2008;Wu, 2006;Girlando and Anderson, 2001). The intent of this current study is to continue the trend.…”
Section: A Re-examination Of Hofstede's Cultural Dimensions With Japamentioning
confidence: 99%